Evaluation of intake charge hydrogen enrichment in a heavy-duty diesel engine - Monemian, Emad; Cairns, Alasdair; Gilmore, Mark; Newman, David; Scott, Keith (Sage, 2017)
Concerns over CO2 emissions and global warming continue to enforce the transport sector to reduce the fuel consumption of heavy duty diesel goods vehicles as one major contributor of CO2. Such powertrain platforms look set to remain the dominant source of heavy duty vehicle propulsion for decades to come. The currently reported work was concerned with experimental evaluation of the potential to partially displace diesel with hydrogen fuel, which continues to attract attention as a potential longer term alternative fuel solution whether produced on-board or remotely via sustainable methods. The single cylinder engine adopted was of 2.0 litre capacity, with common rail diesel fuel injection and EGR typical of current production technology. The work involved fumigation of H2 into the engine intake system at engine loads typically visited under real world driving conditions. Highest practical hydrogen substitution ratios increased indicated efficiency by up to 4.6% at 6bar IMEPn and 2.4% at 12bar IMEPn. In 6bar IMEPn, CO2, CO and soot all reduced by 58%, 83% and 58% respectively while the corresponding reduction of these emissions in 12bar IMEPn, were 27%, 45% and 71% respectively toward diesel-only baseline. Under such conditions the use of a pre-injection prior to the main diesel injection was essential to control the heat release and pressure rise rates.